Thermodynamics in f(T) Gravity with Nonminimal Coupling to Matter - Tahereh Azizi; Najibeh Borhani (Advances in High Energy Physics)
In the present paper, we study the thermodynamics behavior of the field equations for the generalized f(T) gravity with arbitrary coupling between matter and the torsion scalar. In this regard, we explore the verification of the first law of thermodynamics at the apparent horizon of the Friedmann-Robertson-Walker universe in two different perspectives, namely, the nonequilibrium and equilibrium descriptions of thermodynamics. Furthermore, we investigate the validity of the second law of thermodynamics for both descriptions of this scenario with the assumption that the temperature of matter inside the horizon is similar to that of horizon.